2019
DOI: 10.1177/1757177419892072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bundle of care to reduce incisional surgical site infection after gastrointestinal surgery

Abstract: Background: Surgical site infection (SSI) is associated with morbidity, mortality and increased care costs; many SSIs are considered preventable. The aim of the present study was to test implementation of a pragmatic, evidence-based bundle designed to reduce incisional SSI after emergency laparotomy and elective major lower gastrointestinal surgery. Method: This was a prospective before-and-after study. Data were collected before the intervention and for two separate subsequent time periods. An evidence-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Nine of the included studies reported compliance with the SSI prevention bundle (Table 2). Overall, SSI prevention bundle compliance increased over time 19,29,32,34,35,52,53 …”
Section: Resultsmentioning
confidence: 99%
“…Nine of the included studies reported compliance with the SSI prevention bundle (Table 2). Overall, SSI prevention bundle compliance increased over time 19,29,32,34,35,52,53 …”
Section: Resultsmentioning
confidence: 99%
“…Ruiz-Tovar then studied the effects of closure sutures on deep SSI rates, comparing triclosan-coated barbed suture 6.4% with the control of polydioxanone loop suture 16.3% [ 40 ]. Phelan and his cohort of 83 patients, examined the rate of SSI with bundles 26.7% and without bundles 28.3% [ 39 ]. Lastly, Yamamoto, similarly to Phelan, examined the effects of bundles on SSIs, identifying an SSI rate of 20% with a bundle and 42.6% without [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies’ information on patient demographics and indications for surgery were unobtainable as elective and emergency cohorts were not sub categorized [ 31 , 34 , 36 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, the incidence of SSI may respond to bundles of care. For example, a small before and after study, whilst not finding a statistically significant decrease in infections, did find a significant decrease in (costly) re-admissions [ 49 ]. Re-admissions may reflect well the consequences of overall reduced complications rates and costs [ 35 ] as do derived parameters such as days-at-home after surgery (DAH) [ 50 ••].…”
Section: The Measured Costs Of Complicationsmentioning
confidence: 99%